Painted and decorated boats for visarjan - Mumbai Archive Project Team (Jio Institute, 2024)
The fishing boats are specially painted and decorated on the occasion of Narali Purnima, which takes place a few weeks before Jyestha Gauri Puja. The boats are decked with floral garlands and colourful flags as the new fishing season commence at the end of the monsoon season.